Hate Speech and Offensive Speech in Indonesian Law, Alignment with the Rabat Plan of Action (RPA) - Evy Febryani (Eastasouth Institute, 2026)
The regulation of hate speech and offensive speech has become a critical issue within Indonesian law, particularly in the context of expanding digital communication and increasing public discourse on social media platforms. This study aims to examine the normative construction of hate speech and offensive speech in Indonesian legal frameworks and to assess their alignment with the Rabat Action Plan (RPA) through a normative juridical analysis. The research employs doctrinal methods by analyzing statutory provisions, legal principles, and international human rights standards, focusing on the six-part threshold test of the RPA, which includes context, speaker, intent, content or form, extent of dissemination, and likelihood of harm. The findings indicate that Indonesian law demonstrates a strong commitment to maintaining public order and social harmony; however, several legal provisions remain broadly formulated, creating potential overlap between hate speech and offensive speech. The absence of a structured analytical framework may lead to inconsistent interpretation, particularly regarding intent and demonstrable harm. Comparative analysis reveals that while Indonesian regulations share similar objectives with the RPA, greater emphasis on proportionality, contextual assessment, and clear legal thresholds is needed to ensure compatibility with international human rights standards. This study contributes to the discourse on legal harmonization by offering a normative evaluation of speech regulation in Indonesia and highlighting the importance of balancing freedom of expression with the protection of vulnerable groups in the digital era.